Comparing diene derivatisation methods of dry blood spot samples for vitamin D metabolites quantification by liquid chromatography-tandem mass spectrometry - Cromarty, Allan Duncan (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2017.